Penerapan Sistem Point Of Sale (Pos) Dalam Pengelolaan Usaha Dagang PT Trio Karya Makmur Geminar Kota Metro - Natasa, Agnes; Nusantoro, Jawoto; Febri Darmayanti, Elmira (Expensive: Jurnal Akuntansi dan Keuangan, 2024)
This research aims to determine the application of the Point of Sale (Pos) system in the management of the PT Trio Karya Makmur Geminar Metro City trading business. The type of research used is descriptive qualitative research. The instruments used in this research were interviews and observations. Data analysis was carried out using Point of Sale analysis and Management Information System input. The research results show that PT Trio Karya Makmur Geminar Kota Metro has implemented an on-line POS system. This means that every time a sales transaction occurs, it will immediately affect all data in the store. The POS system at PT Trio Karya Makmur Geminar Kota Metro is generally good. This is shown by the compatibility between the POS system in the shop and the theory regarding the POS system. In the Deposit Details and Cashier's Proof of Deposit documents, no printed serial numbers were found. Therefore, recommendations for improvements to these two documents were made.